Algorithm to Convert Signal Interpreted Petri Net Models to Programmable Logic Controller Ladder Logic Diagram Models - Z. Aspar; Nasir Shaikh-Husin; M. Khalil-Hani (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Signal Interpreted Petri Nets (SIPN) modeling has been proposed as an alternative to Ladder Logic Diagram (LLD) modeling for programming complex programmable logic controllers (PLCs) due to its high level of abstraction and functionalities. This paper proposes an algorithm to efficiently convert existing SIPN models to their LLD models equivalences. In order to automate and speed up the conversion process, matrix calculation approach is used. A complex SIPN model was used to show that existing conversion technique must be expanded in order to cater for a more complex SIPN models.